Elements of theory of elasticity: study aid - Svetashkov A. A. Aleksandr Andreevich; Kupriyanov N. A. Nikolay Amvrosievich; Pavlov M. S. Mikhail Sergeevich; Manabaev K. K. Kairat Kamitovich (Tomsk, TPU Publishing House, 2024)
The textbook contains the basic theoretical principles of the theory of elasticity. The basic relationships for describing the stress-strain state at an arbitrary point of an elastic body are presented, the formulation and methods for solving spatial and plane problems of the theory of elasticity are described, the issues of thermoelasticity, contact interaction of elastic bodies, as well as the theory of shells are covered. The textbook is intended for students studying in the areas of training 15.00.00 Machine Engineering and 21.00.00 Applied Geology, Mining, Oil and Gas Engineering and Geodesy.